VD_FINDINFO HC / 2011 / 200 vom 11. April 2011 - VD Tribunal cantonal (2011)
MESURE DE CONTRAINTEDROIT DES ÉTRANGERS | 73 LOJV, 76 al. 1 let. b ch. 3 LEtr, 76 al. 1 let. b ch. 4 LEtr, 79 LEtr, 30 LVLEtr, 31 al. 2 LVLEtr